2019
DOI: 10.1007/s42452-019-0545-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of statistical and soft computing-based predictive models for material removal rate and surface roughness during helium-assisted EDM of D3 die steel

Abstract: This research work proposes mathematical models, based on artificial neural network (ANN) with back-propagation algorithm, adaptive neuro-fuzzy inference system (ANFIS) and response surface methodology (RSM), for prediction of material removal rate (MRR) and surface roughness (SR) of helium-assisted electrical discharge machining of D3 die steel. The helium gas-assisted die-sinking EDM with perforated electrode was carried out by an EDM machine. For the present experimental work, discharge current, pulse on ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Finding reveals that developed model predict the process output with minimum mean error. Singh et al [25] developed statistical and soft computing-based models and performed the comparative studies during EDM of die steel. Finding suggested that actual and values predicted by developed models are in good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Finding reveals that developed model predict the process output with minimum mean error. Singh et al [25] developed statistical and soft computing-based models and performed the comparative studies during EDM of die steel. Finding suggested that actual and values predicted by developed models are in good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…3.1 Electrode selection for machining of AZ91/5B4C composites EDM was specifically used for the machining of hard materials (Ahmed et al, 2019). An enormous amount of research work has been carried out with the goal of finding an optimal process parameter by varying the input variables of EDM (Singh et al, 2019;Nair et al, 2019). The machining characteristic of EDM depends greatly on the selection of the right combination of the electrode and the tool material.…”
Section: Decision-making Problemsmentioning
confidence: 99%
“…Two groups of experiments were performed, just with the kerosene dielectric and then by adding the SiC micro powders mixing to dielectric uid. Singh [14] studied the statistical and soft computer-based predictive models for the surface roughness (SR) and material removal rate (MRR) during the EDM process of die steel which was helium-assisted. They tried to develop mathematical models to predict the MRR and SR.…”
Section: Introductionmentioning
confidence: 99%